Pengaruh Motivasi Kerja dan Kepuasan Kerja Terhadap Kinerja Karyawan pada PT. Supraco Lines - Chintya Mei Dina Dewi (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2024)
Work motivation and job satisfaction are important things to improve performance. Work motivation provides a driving force that produces enthusiasm for work so that they want to collaborate, work effectively, and combine all efforts to achieve satisfaction (Hasibuan, 2018: 65), while job satisfaction is a positive behavior of a worker towards his job (Afandi, 2018: 74). This research focuses on proving the effect of work motivation and satisfaction on the performance of PT Supraco Lines employees. This research system is qualitative research that is converted to a quantitative scale using multiple linear regression analysis with PT Supraco Lines employees as objects. The sample of this study was 50 respondents, using path analysis, this study tested 3 hypotheses. From the results of the research showed that work motivation and job satisfaction could not affect employee performance partially, but when the two variables were tested simultaneously, the results were able to significantly affect the job satisfaction of PT Supraco Lines employees.